Thermal Conductivity of Ethylene Glycol Based Copper Nanoparticle Decorated Graphene Nanofluids - Van Trinh, Pham; Ngoc Anh, Nguyen; Dinh Quang, Le; Hung Thang, Bui; Ngoc Hong, Phan; Tuan Hong, Nguyen; Hong Khoi, Phan; Ngoc Minh, Phan (Communications in Physics, 2017)
In this paper, thermal conductivity of ethylene glycol based copper nanoparticle decorated graphene (Cu/Gr) nanofluids are successfully synthesized by a chemical reduction tecnique using ascorbic acid antioxidant agent. Nano-sized copper nanoparticles is decorated on functionalized graphene, and then dispersed uniformly in ethylene glycol (EG) to make the nanofluids. Morphology, phase composition and thermal conductivity of nanofluids are investigated in detail. Thermal conductivity of nanofluid containg Cu/Gr with mass ratio of 5:1 shows an enhancement about 10% and 29% at 30oC and 60oC comparing with EG fluid only. The results show the high potential application of Cu/Gr nanofluid in heat transfer fields